IDENTIFICATION OF ALTERNATIVE LANDFILL SITE USING QGIS IN A DENSELY POPULATED METROPOLITAN AREA - Sheoran, Savita Kumari; Parmar, Vinti (Quaestiones Geographicae, 2020)
Appropriate landfill site selection for disposal of solid waste is a very complicated assignment, as it needs multicriteria analysis of various parameters. In this study, we have used QGIS for identification of alternative landfill site in Gurugram district, a satellite city of New Delhi. Various criteria are analysed for selecting the landfill sites. Weight and rank are assigned to the criterion such as road networks, presence of water bodies, residential locations, and depth of the underground water table by using the Analytic Hierarchy Process (AHP). Five possible landfill sites have been identified for solid waste disposal based upon the AHP method analysis and overlay analysis in GIS tool in Gurugram district. The methodology used in this paper is very efficient for performing multicriteria analysis and can be generalised for selecting landfill sites in other areas with similar demographics.